2022
DOI: 10.1111/fme.12567
|View full text |Cite
|
Sign up to set email alerts
|

Review of adaptations of U.S. Commercial Fisheries in response to the COVID‐19 pandemic using the ResistAcceptDirect (RAD) framework

Abstract: The COVID‐19 pandemic transformed social and economic systems globally, including fisheries systems. Decreases in seafood demand, supply chain disruptions, and public safety regulations required numerous adaptations to maintain the livelihoods and social resilience of fishing communities. Surveys, interviews, and focus groups were undertaken to assess impacts from and adaptive responses to the pandemic in commercial fisheries in five U.S. regions: the Northeast, California, Alaska, the U.S. Caribbean, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Meanwhile, Ramanathan et al [17] proposed 15 strategies to food, sports, and fashion SC managers for facilitating the response before, during, and after the COVID-19 pandemic. Smith et al [18] stated that fish merchants in the United States responded to the COVID-19 pandemic by developing strategies such as sharing and hiring new crew, donating fish to humanitarian organizations, and improving communication between fishermen and fish processors. Zhang et al [19] reported how specific SC management strategies such as effective and reliable leadership, unity of purpose, integrated and strong digital infrastructure and capabilities, constant learning, and the development of resilience were essential in the response of the personal protective equipment company in British Columbia.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Ramanathan et al [17] proposed 15 strategies to food, sports, and fashion SC managers for facilitating the response before, during, and after the COVID-19 pandemic. Smith et al [18] stated that fish merchants in the United States responded to the COVID-19 pandemic by developing strategies such as sharing and hiring new crew, donating fish to humanitarian organizations, and improving communication between fishermen and fish processors. Zhang et al [19] reported how specific SC management strategies such as effective and reliable leadership, unity of purpose, integrated and strong digital infrastructure and capabilities, constant learning, and the development of resilience were essential in the response of the personal protective equipment company in British Columbia.…”
Section: Introductionmentioning
confidence: 99%